О расположении коней в кургане Козёл - Переводчикова, Е.В.; Фирсов, К.Б. (Археологія і давня історія України, 2019)
Статья посвящена изучению особенностей расположения конских погребений в скифском царском
кургане Козёл IV в. до н. э., раскопанном И. Е. Забелиным в 1865 г. В научный оборот вводятся письменные источники по исследованию памятника. Материалы кургана Козёл сравниваются с соответствующими данными из кургана Чертомлык,
где найдены подобные конские могилы. The article deals with the disposition of horses in
Kozel barrow of the IV century BC situated in the left
coast Lower Dnieper region. 11 horses were buried in
three special tombs there. The horses were adorned
with silver and bronze bridles, some had also saddles with golden plagues, and some had bronze breast
(neck) dressings. I. E. Zabelin, the author of excavation this barrow,
had described the disposition of horses. We had analyzed the arrangement of horses on the basis of this
description. We had seen some rhythm in the arrangement of the horses in silver and bronze dressings. The
regularity observed was based on the colour difference of horse bridles. Comparing the results of our observations
on the Kozel horses disposition with the disposition of horses in Chertomlyk barrow we had found
some resemblance between them also basing on the colour difference of horse bridles.
A. Yu. Alexeev analyzing Chertomlyk horse tombs became to a conclusion this way of space organization
of horse tombs is an evidence of royal status of the buried person. This conclusion may be applied for
Kozel barrow also, but it is smaller and not so rich, and usually is interpreted as a burial of royal family member.
But we should not forgot that nobody knows of the treasures contained this plundered barrow.